Use Markers of Short Tandem Repeats (STR) for Samples of Bone in the Forensic Diagnosis of the Human Being in the in Kerbala Governorate (Indian Journal of Forensic Medicine & Toxicology, 2020)
STR’s analysis of DNA from bone samples plays an important role in identifying missing persons. We presenta method for DNA extraction from bone samples that involve complete demineralization and digestion ofthe sample, followed by purification by silica binding. This method, along with the multiple STR typingapproach, has also proven highly successful in recovering DNA profiles from bone samples from a widerange of contexts. These methodological steps include bone cutting and grinding, DNA extraction, Repurification in case of highly inhibited samples, quantification, amplification multiplex STR, Data Analysisof the DNA Typing and The guidelines for the preparation of personal reports. the total number of studysamples reached 48, whose ages ranged between (14 to 33) years divided into 3 groups, group (1) in which(16) bone samples from the son, group (2) in which (16) blood samples from the father and group (3) Itcontains (16) blood samples from the mother. Conformity was carried out in the identification tests forpersons in the forensic evidence laboratories of the Iraqi Ministry of the Interior, according to the protocolsin the Kits used and by forensic experts.